2015
DOI: 10.4102/sajbm.v46i2.90
|View full text |Cite
|
Sign up to set email alerts
|

Managing visitors’ dining and retail experiences in South African national parks

Abstract: In the light of the issue of declining government funding of South African National Parks (SANParks), as well as the negative influence of the poor service levels in shops, restaurants and eating facilities in these parks on visitor spending, SANParks needs to improve the retail and dining experiences at these facilities. This research attempts to provide guidelines for SANParks management in addressing these issues, by determining visitors’ retail and dining preferences and the relationship between these cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…A correcting managerial process to standardize more of these services should be introduced in the near future. Research by Engelbrecht et al (2014) and Kruger et al (2015) has also alluded to some of these variables that require more attention from park management, thereby confirming the areas that require more intervention.…”
Section: Resultsmentioning
confidence: 91%
“…A correcting managerial process to standardize more of these services should be introduced in the near future. Research by Engelbrecht et al (2014) and Kruger et al (2015) has also alluded to some of these variables that require more attention from park management, thereby confirming the areas that require more intervention.…”
Section: Resultsmentioning
confidence: 91%
“…Item Q13 'Food is freshly served', which fell under the restaurant health factor, was moved to the food factor because of its applicability to that category. A similar procedure was performed in the study by Kruger, Saayman and Slabbert (2015), where some factors were retained as part of the alternative possibility. The resulting internal consistency remained acceptable for all the factors, as shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Simon took Canadian brand promotion activities as an example and proposed that tourists’ perceptions of destination information and promotion had a significant impact on tourism experience memory [ 41 ]. Kruger et al found that tourism experience memory was affected by the quality of information about food and entertainment, and of promotional material [ 42 ]. Papyrina proposed that advertising information is used as an external stimulus to resonate with consumers’ imagination, arouse tourists’ emotions, and convey specific memories of the pre-visit experience [ 43 ].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%